In situ Measurement of the Adhesion Strength and Effective Elastic Stiffness of Single Soft Micropillar - Lee, Ji Yeong; Seong, Won Kyung; Choi, In-Suk; Ghosh, Ranajay; Vaziri, Ashkan; Yang, Cheol-Woong; Lee, Kwang-Ryeol; Moon, Myoung-Woon (TAYLOR & FRANCIS LTD, 2015)
We report the deformation behavior and mechanical properties of a polymeric micropillar, which measures approximately 10 mu m by 30 mu m in size by measuring the loading/unloading response using an in situ force measurement system. When the single poly(dimethylsiloxane) (PDMS) micropillar was subjected to compression, we observed a periodic wrinkle and global (Euler) buckling at the sidewall. During unloading, we found the pull-off force (adhesion force) to increase for higher values of preloading and also for lower loading/unloading rates. From the slope of the load-displacement curves measured in situ, we calculated the effective elastic stiffness of the PDMS micropillar to be about 2.03MPa. In addition to the current work, we report that this method can be used more broadly for in situ measurement of the intrinsic mechanical and adhesion properties of polymers and other relatively soft materials.
Keywords: ASPECT RATIO; SENSOR